Treatment of bisphosphonate related osteonecrosis following root canal therapy at the 1-year follow-up: report of two cases - Kaptan F; Kazandag MK; Iseri U (Dove Medical Press, 2013)
Figen Kaptan,1 Meric Karapinar Kazandag,1 Ufuk Iseri21Yeditepe University, Faculty of Dentistry, Department of Endodontics, 2Department of Prosthodontics, Istanbul, TurkeyAbstract: The objective of this report was to use topical gaseous ozone as an adjunct to conventional treatment methods and to describe the multidisciplinary management of bisphosphonate associated bone necrosis, which developed following endodontic treatment. No complaints were noted by the patients at their 1-year follow-up and the treatment showed favorable prognosis.Keywords: bisphosphonate, osteonecrosis, BRONJ, endodontics, oxygen, ozone